ASESMEN TERPADU DALAM RANGKA MENDUKUNG KEBIJAKAN REHABILITASI PENYALAH GUNA NARKOBA - Dindin Supratman; Purwoko Nugroho; Retno Dewi Wijayanti (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
The rise of narcotics abuse in Indonesia, reaching a prevalence of 1.77% in 2017, certainly requires serious treatment. One of the efforts made is the curative approach, which since the Joint Regulation was issued in 2015, the Integrated Assessment Team (TAT) program has been carried out. The purpose of this study was to analyze the effectiveness of the TAT program at BNNK in South Jakarta, as the BNNK that showed over-achievement until 2018. The research method is quantitative descriptive, where sampling uses a purposive sampling method, involving 34 respondents. Data was collected using a questionnaire which was then analyzed using the Factor Analysis test with the application of IBM SPSS 23 and Lisrel 8.8 and the Linear Regression test with IBM SPSS 23. The results showed the TAT program at BNNK South Jakarta was positively influenced by 3 components with an effectiveness level reaching 75.7 %. Another factor expected to influence the effectiveness of the TAT program is coordination, according to the results of interviews with the South Jakarta BNNK TAT team.